UJI EFEK ANTIHIPERTENSI EKSTRAK ETANOL DAUN SELEDRI (Apium graveolens L. ) PADA TIKUS PUTIH JANTAN DIINDUKSI PREDNISON DAN NaCl - Nessa Nessa; Sanubari Rela Tobat; M Husni Mukhtar; Sufi Auliya Muztika (Jurnal Akademi Farmasi Prayoga, 2018)
This study used celery ethanol extract (Apium graveolens L. ) which is expected to reduce blood pressure in rat body previously induced with prednisone 1.5 mg / kgBW and 2.5% NaCl. The test animals were divided into 6 groups, each group consisting of 3 male white rats. Group 1 is a negative control group given susension Na CMC 0,5%. Group 2 was a positive control group given prednisone 1.5 mg / kgBW and 2.5% NaCl. Group 3, 4, 5 were treated with ethanol extract of celery leaves with 3 dose variations (100; 200 and 400) mg / kgBW. Group 6 was the comparison group given Captopril 2.5 mg / kgBB. Treatment was performed for 10 days, observed on day 7 and 10 using a CODA Non-Invasive blood pressure gauge. From the research done in get the result of blood pressure group leverage 1: (121,85 / 99,21 mmHg). Group 2:(159,85 / 136,25 mmHg). Group 3:(120,35 / 94,71mmHg). Group 4:(109.335 / 82.51 mmHg). Group 5:(107.59 / 74.94 mmHg)and Group 6:(117.19 / 95.94 mmHg). The results of this study showed that ethanol extract of celery leaves can lower blood pressure to normal at doses of 100 mg / KgBW compared to other doses. Based on statistical test of variance analysis using ANOVA one way, it was found that ethanol extract of celery leaves significantly affected blood pressure (P <0,05).